2009
DOI: 10.1111/j.1741-3737.2009.00637.x
|View full text |Cite
|
Sign up to set email alerts
|

Communicative Correlates of Satisfaction, Family Identity, and Group Salience in Multiracial/Ethnic Families

Abstract: Guided by the Common Ingroup Identity Model (S. L. Gaertner & J. F. Dovidio, 2000) and Communication Accommodation Theory (C. Shepard, H. Giles, & B. A. LePoire, 2001), we examined the role of identity accommodation, supportive communication, and self‐disclosure in predicting relational satisfaction, shared family identity, and group salience in multiracial/ethnic families. Additionally, we analyzed the association between group salience and relational outcomes as well as the moderating roles of multiracial/et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(66 citation statements)
references
References 29 publications
2
64
0
Order By: Relevance
“…Three behaviors specific to religious talk within families are highlighted in the present study based on previous intergroup research (e.g., Harwood, 2000;Soliz, Thorson, & Rittenour, 2009) and relevance to the current context: inappropriate self-disclosure, emphasizing divergent values, and giving unwanted advice. Inappropriate self-disclosure occurs when individuals offer excessive and unwanted information about their religious experience.…”
Section: Nonaccommodative Communication In Parent-child Relationshipsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three behaviors specific to religious talk within families are highlighted in the present study based on previous intergroup research (e.g., Harwood, 2000;Soliz, Thorson, & Rittenour, 2009) and relevance to the current context: inappropriate self-disclosure, emphasizing divergent values, and giving unwanted advice. Inappropriate self-disclosure occurs when individuals offer excessive and unwanted information about their religious experience.…”
Section: Nonaccommodative Communication In Parent-child Relationshipsmentioning
confidence: 99%
“…There are numerous ways to categorize accommodative behaviors such as the degree to which one manages discourse by selecting appropriate topics of conversation, controls the conversation through body language and interruptions, and adapts the selection and delivery of verbal communication to increase interpretability (Harwood, Soliz, & Lin, 2006); the interpretation of what is considered to be accommodative is dependent upon the context and skill of the communicators. In the present study, we target two accommodation behaviors demonstrated to be important in other family research taking an intergroup approach (e.g., Harwood, 2000;Soliz, Thorson, & Rittenour, 2009) and relevant to religious difference: religious-specific supportive communication and respecting divergent values.…”
Section: Accommodative Communication In Parent-child Relationshipsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although relatively limited, a more concerted effort to include individuals with multiple ethnic backgrounds is appearing in the research on ethnic identity. Building on some of the early work on multiethnic experiences (e.g., Root, 1996) and using theories from the social identity tradition and more critical theories (e.g., complicity theory, performance theories), scholars have focused their attention on understanding how individuals embrace and express multiethnic identity (Moreman, 2011;Orbe & Drummond, 2007;Rockquemore & Brunsma, 2002), family communication and ethnic diversity (Orbe, 1999;Soliz, Thorson, & Rittenour, 2009), and well-being (Sanchez, Shih, & Garcia, 2009). Emerging from this research is the complexity situated in the development, negotiation, and expression of ethnic identity.…”
mentioning
confidence: 99%